Language choice and identity of tertiary level Malay ESL learners / Widad Abdul Ghafar - Widad, Abdul Ghafar (2017)
Code choice seems to be a common everyday experience in a multilingual society like Malaysia. The present study determines the choice of code for 30 Malay ESL learners from Kelantan, Terengganu and Kedah. Three specific domains namely home, university and social network have been identified as domains for reasons of their choice in relation to their identity. This study adopts a survey questionnaire as the main method of collecting data and interview method to discover the factors and reasons that can affect their choice of code. It also explores the issue of identity that may become one of the factors for the chosen code based on the Social Identity Theory. The findings reveal that English is mostly spoken in university and social network domains whilst the local dialect is the dominant code used in home domain. It further shows that English has no significant effect on the construction of identity rather; identity is nurtured by the participants’ background, sense of pride in their heritage and linguistic behaviour. However, the results and findings could not be generalised to a bigger population as this study only focuses on Malay learners from the three states. The samples involved are only from four local universities thus, the data is rather small.